Implementasi Metode Ceramah Dalam Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam di SMAN 1 Lareh Sago Halaban - Fardilah, Ega; Ariza, Hidra; Sufyan , Muhammad (Indonesian Research Journal on Education, 2023)
The learning method is a crucial component in the learning process. Appropriate learning methods can improve student learning outcomes. One method that is often used in learning is the lecture method. However, many people find this lecture method boring, watching, does not make students active, the material cannot be digested properly. From this phenomenon, the researcher aims to explain the implementation of the lecture method in improving learning outcomes in Islamic religious education subjects at SMA N 1 Lareh Sago Halaban. This research uses a qualitative descriptive approach with field research, namely research that examines facts and collects data that occurs in the field using data collection techniques through observation and interviews. Based on the research conducted, the researchers concluded that the implementation of the lecture method in improving learning outcomes inIslamic religious education subjects had their respective strengths and weaknesses. The advantages of using this lecture method are that the lecture method is very effective if the number of students is quite large, while the drawback of this lecture method is that students become bored if the teacher explains learning material does not use media which is used as a support for the process in implementing the lecture method in class. The lecture method also influences student learning outcomes obtained in class.The learning outcomes obtained by students in Islamic religious education subjects are sufficient for the KKM (minimum completeness criteria) that has been set.